Acute kidney injury in the era of big data: the 15th Consensus Conference of the Acute Dialysis Quality Initiative (ADQI). Issue 1 (December 2016) - Bagshaw, Sean; Goldstein, Stuart; Ronco, Claudio; Kellum, John
Abstract The world is immersed in "big data ". Big data has brought about radical innovations in the methods used to capture, transfer, store and analyze the vast quantities of data generated every minute of every day. At the same time; however, it has also become far easier and relatively inexpensive to do so. Rapidly transforming, integrating and applying this large volume and variety of data are what underlie the future of big data. The application of big data and predictive analytics in healthcare holds great promise to drive innovation, reduce cost and improve patient outcomes, health services operations and value. Acute kidney injury (AKI) may be an ideal syndrome from which various dimensions and applications built within the context of big data may influence the structure of services delivery, care processes and outcomes for patients. The use of innovative forms of "information technology" was originally identified by the Acute Dialysis Quality Initiative (ADQI) in 2002 as a core concept in need of attention to improve the care and outcomes for patients with AKI. For this 15th ADQI consensus meeting held on September 6–8, 2015 in Banff, Canada, five topics focused on AKI and acute renal replacement therapy were developed where extensive applications for use of big data were recognized and/or foreseen. In this series of articles in theCanadian Journal of Kidney Health and Disease, we describe the output from these discussions. ABRÉGÉ Le monde nage actuellement dans une mer de données informatiques. L'apparition de mégadonnées a entraîné des changements majeurs dans la façon de saisir, de transférer, de stocker et d'analyser la multitude de données générée chaque minute de chaque jour. Parallèlement, il est aussi plus facile de gérer ces informations et de le faire à un coût relativement moindre. La capacité de transformer, d'intégrer et d'appliquer rapidement la variété et le volume considérable de données est ce sur quoi repose le futur des mégadonnées. Le traitement des mégadonnées ainsi que leur analyse prévisionnelle dans le système de santé se veut très prometteur pour favoriser l'innovation, réduire les coûts, apporter des changements favorables au fonctionnement et à la portée des services ainsi que pour améliorer le pronostic des patients. Il semble que l'insuffisance rénale aiguë (IRA) soit un syndrome idéal à partir duquel les différents aspects et applications mis en place pour gérer les mégadonnées pourraient influencer les modèles existants de prestation de services et d'offre de soins et, par extension, l'évolution de l'état de santé des patients. L'utilisation de formes novatrices pour assimiler les technologies et l'information a d'abord été identifiée en 2002 par l'Acute Dialysis Quality Initiative (ADQI) en tant que concept nécessitant une attention particulière et qui pourrait améliorer les soins et le pronostic des patients atteints d'IRA. Lors de la 15e réunion annuelle de concertation de l'ADQI qui s'est tenue du 6 au 8 septembre 2015 à Banff, au Canada, on a mis l'accent sur cinq thèmes reliés à l'IRA et aux thérapies de remplacement rénal. Ils ont été développés dans des cadres où l'on reconnaissait ou prévoyait l'application étendue des mégadonnées. Dans une série d'articles qui paraîtra dans leCanadian Journal of Kidney Health and Disease, nous ferons ressortir les conclusions de ces discussions.